Provisional and protective measures in child return procedures: analysis of Regulation (EU) 2019/1111 in conection with the Spanish legal system - Calzado Llamas, Antonio Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The present article encompasses the study of provisional, including protective measures in children return procedures according to the new Regulation (EU) 2019/1111 regime. Beginning with the analysis of its article 15, we focus on its application in two procedural moments as a result of an illegal removal or retention: the maintenance of contact with the custodial parent, and protective measures against any grave risk in case of return to the State of habitual residence. The occasion is seized to evaluate the linkage of European recasts with the Spanish legislation. Finally, we take into consideration the existence of preventive measures in conventional, European and national Law in order to avoid international child abduction.
Keywords: international child abduction; Regulation 2019/1111; 1980 Hague Convention; provisional and protective measures; preventive measures